2022
DOI: 10.1017/s095927092100054x
|View full text |Cite
|
Sign up to set email alerts
|

Trade in vulture parts in West Africa: Burkina Faso may be one of the main sources of vulture carcasses

Abstract: Summary The current catastrophic decline in African vultures is caused mainly by poisoning, and killing for consumption and belief-based use (traditional medicine). To find out more about the key threats to vultures in West Africa, we assessed the main anthropogenic causes of vulture mortality in Burkina Faso. We analysed incidents of mass vulture mortality, based on interviews conducted in 2016 with local butchers, veterinarians, foresters, and abattoir watchmen at 44 sites across the country. A total of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Our results have shown that poaching (with poisoned baits, guns and traps) and decreasing food availability are the most important threats for Hooded Vultures in northern Benin and elsewhere in West Africa (Daboné et al, 2023). It is important that these threats F I G U R E 5 Knowledge about the causes of Hooded Vulture declines.…”
Section: Cons Ervation Implic Ationmentioning
confidence: 81%
See 1 more Smart Citation
“…Our results have shown that poaching (with poisoned baits, guns and traps) and decreasing food availability are the most important threats for Hooded Vultures in northern Benin and elsewhere in West Africa (Daboné et al, 2023). It is important that these threats F I G U R E 5 Knowledge about the causes of Hooded Vulture declines.…”
Section: Cons Ervation Implic Ationmentioning
confidence: 81%
“…In Benin, all vulture species are protected by several legislative decrees of which the most recent is the N° 2011-394 of 28 and any person infringing this provision shall be liable to sentences ranging from 3 months to 3 years and/or to a fine of 100,000 to 500,000 CFA (~ USD 160-830). Nevertheless, while performing fieldwork, we were occasionally mistaken for poachers or traders, and offered vulture carcasses for 60,000-100,000 CFA (~ USD 100-160) each, which is 12-20 times the usual price paid in Burkina Faso (Daboné et al, 2023). Furthermore, we encountered a traditional healer living in Nikki locality with two live Hooded Vultures in a cage, who had declined several offers from Nigerians of up to 300,000 CFA (~ USD 500) for a live Hooded Vulture.…”
Section: Threats To Hooded Vulturesmentioning
confidence: 99%
“…Direct persecution, whereby vultures are victims of deliberate illegal killing driven by dislike or superstition (Botha et al 2017), is not the main driver of global vulture decline but can become locally frequent and have a large impact on several species (Brochet et al 2019, Cailly Arnulphi et al 2017, Daboné et al 2023, Oppel et al 2021). Indirect anthropogenic mortality also represents a major threat to vultures (Arrondo et al 2020, Berny et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we explore the status of Hooded Vulture outside of protected areas, in northern Benin, by using roadside surveys.With the high level of demand for vulture body parts in Benin and Nigeria (a neighbouring country of Benin) (Nikolaus 2011;Buij et al 2016) and particularly, the recent increasing pro tability of the regional trade in vulture body parts (Buijet al. 2016;Daboné et al 2022a), we expected that Hooded Vulture would have become rare, with poaching for belief-based use being the main threat to Hooded Vultures in this area.…”
mentioning
confidence: 99%
“…In the light of this, it appears that Hooded Vultures are severely declining in their West African range, but still survive locally in some restricted areas. Where large densities of vultures still occur, there has been a rapid rise in reports of vultures killed using poisoned baits for trade and beliefbased use(Henriques et al 2020;Daboné et al 2022a); this situation is alarming and presents a serious conservation challenge for Hooded Vultures in this region. Su cient attention has to be paid to the overall situation for Hooded Vultures in West Africa, before any attempt to down-list the conservation status of this bird to Endangered on the IUCN Red List of Threatened Species.…”
mentioning
confidence: 99%